2006
DOI: 10.1128/jvi.00605-06
|View full text |Cite
|
Sign up to set email alerts
|

Cidofovir Resistance in Vaccinia Virus Is Linked to Diminished Virulencein Mice

Abstract: Cidofovir [(S)-1-(3-hydroxy-2-phosphonylmethoxypropyl)cytosine (HPMPC)] is recognized as a promising drug for the treatment of poxvirus infections, but drug resistance can arise by a mechanism that is poorly understood. We show here that in vitro selection for high levels of resistance to HPMPC produces viruses encoding two substitution mutations in the virus DNA polymerase (E9L) gene. These mutations are located within the regions of the gene encoding the 3-5 exonuclease (A314T) and polymerase (A684V) catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
147
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(157 citation statements)
references
References 39 publications
9
147
0
1
Order By: Relevance
“…Several in vitro studies with purified DNA polymerase of human cytomegalovirus and VACV (33,34,55), and in vivo studies with CDV-resistant viruses (2,5,28,45) have pointed to virus DNA replication as the main target for CDV action. However, no detailed analysis of the effect of CDV on the VACV replicative cycle has ever been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies with purified DNA polymerase of human cytomegalovirus and VACV (33,34,55), and in vivo studies with CDV-resistant viruses (2,5,28,45) have pointed to virus DNA replication as the main target for CDV action. However, no detailed analysis of the effect of CDV on the VACV replicative cycle has ever been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the effects of CDV on human cytomegalovirus (55) and VACV enzymes have been observed, but overall it has been widely accepted that CDV acts by inhibiting the process of virus DNA replication. Moreover, most CDV-resistant VACV strains contain mutations in the catalytic domain or in the 3Ј-5Ј exonuclease domain of the DNA polymerase (2,5,28,45).…”
mentioning
confidence: 99%
“…The cell and virus culture methods used in this study have been described elsewhere (1). Wild-type VAC and its CDV r derivatives were obtained as described previously (1) and are derived from a stock of VAC (strain WR) originally acquired from the American Type Culture Collection. Viruses carrying temperature-sensitive mutations in the E9L gene (Dts83 and Cts42) were obtained from R. Condit (Gainesville, FL).…”
Section: Methodsmentioning
confidence: 99%
“…However, we have developed a novel, antiviral-based strategy for the study of the role of E9 in viral recombination. This approach was developed from our previous studies of the mechanism of action of the dCMP analog cidofovir {(S)-1-[3-hydroxy-2-(phosphonylmethoxypropyl) cytosine]} (CDV) (34,35) as well as through the characterization of CDV-resistant (CDV r ) VAC strains (1). We have previously shown that VAC DNA polymerase can use the diphosphoryl metabolite of CDV (CDVpp) as a substrate and faithfully incorporate a CDV residue opposite dGMP in the template strand (35).…”
mentioning
confidence: 99%
“…Compounds that show promise in preclinical or clinical settings are the cidofovir derivative CMX001 (24), which is a nucleoside analog, and ST-246 (12,13), which has a unique mechanism of action in preventing viral egress from infected cells. With the majority of inhibitors, including CMX001 and ST-246, viral resistance is achieved rapidly in cell culture (1,9,33). As with many antimicrobial strategies, effective treatment is likely to require combination therapy.…”
mentioning
confidence: 99%